In vitro and in vivo Induction of p53-Dependent Apoptosis by Extract of Euryale ferox Salisb in A549 Human Caucasian Lung Carcinoma Cancer Cells Is Mediated Through Akt Signaling Pathway - Nam, Gun-He; Jo, Kyung-Jo; Park, Ye-Seul; Kawk, Hye Won; Kim, Sang-Yong; Kim, Young-Min (Frontiers in Oncology, 2019)
Lung cancer is one of the biggest causes of death worldwide, and mortality rates have been steadily increasing. Several studies have recently been conducted to develop novel, physiologically active compounds from medicinal plant extracts. Several plant-derived extracts and molecules inhibit and regulate signaling molecules associated with the growth and proliferation of cancer cells. Euryale ferox salisb is a medicinal plant that is effective against different types of cancers. In this study, we investigated the apoptotic effects of E. ferox salisb extract (ESE) in A549 lung cancer cells, exerted by the inhibition of the Akt protein and activation of the p53 protein. Our results show that ESE induces apoptosis via the regulation of mitochondrial outer membrane potential and generation of reactive oxygen species (ROS). We demonstrate that apoptosis is induced in a p53-dependent manner when cells were treated with pifithrin-α (a p53 inhibitor) and LY294002 (an Akt inhibitor). The apoptotic effects from ESE were observed in vivo in Balb/c-nu mice bearing A549 xenografts. Taken together, these results suggest that E. ferox salisb extracts exert anticancer effects in a p53-dependent manner.